MULTIDIMENSIONAL BURDEN of STUNTING in CHILDREN UNDER FIVE: A SYSTEMATIC REVIEUW of INDIVIDUAL, HOUSEHOLD, and COMMUNITY RISK FACTORS - Etik Sulistyorini; Fitria Hayu Palupi; Ropitasari Ropitasari; Sri Handayani; Evi Widowati; Ani Nur Fauziah (Jurnal Kebidanan Indonesia, 2026)
Background: Stunting among children under five remains a major public health concern, particularly in low- and middle-income countries. It reflects chronic undernutrition and is associated with impaired cognitive development, poor educational outcomes, and long-term socioeconomic disadvantages. Due to its complex and multilevel etiology, a comprehensive understanding of contributing factors is essential for effective intervention strategies. This study aims to systematically review and synthesize evidence on the determinants of stunting in children under five, focusing on risk factors at individual, household, and community levels.. Subjects and Method: A systematic literature search was conducted using databases including SpringerLink, ScienceDirect, Sage, and Taylor & Francis. Keywords such as “stunting,” “growth retardation,” “risk factor,” and “children under five” were applied. Articles were selected based on the PICO framework, with inclusion criteria limited to full-text, quantitative studies published between 2020 and 2025, focusing on children aged 0–59 months. A total of 23 eligible articles was guided by a PRISMA flow diagram and were analyzed using thematic narrative synthesis.Results: At the individual level, factors such as low dietary diversity, male gender, low birth weight, and inadequate immunization were associated with higher risk. At the household level, maternal education, household wealth, food insecurity, and poor sanitation were significant predictors. At the community level, geographic location, limited access to health services, and environmental conditions (e.g., water safety, sanitation) were critical contributors. Several studies employed multilevel and machine learning analyses, reinforcing the interrelated nature of risk factors. However, there remains a gap in longitudinal evidence, father involvement, and evaluation of integrated interventions.Conclusion: This review confirms the multifactorial nature of stunting and highlights the urgent need for context-specific, multisectoral strategies. Interventions should integrate nutrition education, WASH, maternal and child health, and poverty alleviation. Future studies should incorporate longitudinal, behavioral, and programmatic evaluations to better inform public health policy.